MDR1 Gene Polymorphisms and Its Association With Expression as a Clinical Relevance in Terms of Response to Chemotherapy and Prognosis in Ovarian Cancer - Haque, Absarul; Sait, Khalid Hussain Wali; Alam, Qamre; Alam, Mohammad Zubair; Anfinan, Nisreen; Wali, Abdul Wahab Noor; Rasool, Mahmood (Frontiers in Genetics, 2020)
In spite of the significant advancements in the treatment modalities, 30% of advanced stage ovarian cancer (OC) patients do not respond to standard chemotherapeutic regimen and most of the responders finally relapse over time due to the escalation of multidrug resistance (MDR) Phenomenon. Our present study first evaluated chemotherapeutic sensitivity response among 47 ovarian tumor patients of which we found 37 (78.8%) sensitive and remaining 10 (21.2%) resistant. Among resistant, seven tumor samples were found platinum resistant or refractory to platinum (CB/TX), one to carboplatin, two to 5FU. Notably, all these resistant cases were observed in the disease recurrence group of patients identified in stage III or IV. The stage III resistant cases revealed heterozygous mutation (C/T) in exon 12 (C1236T) and 26 (C3435T) and increased level of mRNA, whereas homozygous mutation (T/T) was found with stage IV tumor patients. The genotypic difference was significant (P=0.03) for exon 12, and P=0.003 for exon 26 mutant genotypes when ovarian tumor samples were compared with healthy controls. No significant association between genotypes of different exons with tumor stages and tumor grade was observed (p>0.05). However, a significant association was observed between genotype of exon-12 and histopathology of tumor tissue (P=0.028). Statistically, the chemotherapy response was found significantly associated with the tumor stage (p= 0.019). We also observed a significant difference in PFS (P=0.019) and OS (P=0.047) between tumor grade 1 and 3. Notably, highest mRNA expression was observed in resistant tumor sample T-32, where interestingly we found homozygosity TT in all of the exons 12, 21 and 26. Thus, we suggest that exon 12 (C1236T) and exon 26 (C3435T) polymorphism may play a role in inducing drug resistance by altering the expression level of the MDR1 gene. To summarize, we suggest that the expression of MDR1 in ovarian cancer is influenced by tumor stage and genotype variants as well as by chemotherapeutic drugs. Thus our findings suggest that inter individual variability in platinum based therapy may be anticipated by MDR1 genotypes. Further studies on large number of samples eventually shall lead to provide beneficial information for individualized chemotherapy.